Comment on Mary Anne Case's Enforcing Bargains in an Ongoing Marriage - Robert A. Pollak (Washington University Journal of Law & Policy, 2011)
The author discusses the article “Enforcing Bargains in an Ongoing Marriage,” by Mary Anne Case, regarding the “love-it-or-leave it” rule in marriage. He states that economic models such as the unitary model and the altruist model of Gary Becker exaggerate the chances that inefficiencies would rise without legal enforceability. Furthermore, the exaggerations are caused by the ignored mechanisms of the models such as the internalized norms, self-help, and non-legal third-party enforcement.
Keywords: Husband & wife; Domestic relations; Law & economics; Divorce mediation; Marital separation; Prenuptial agreements; Nebraska